Pre-targeting with ultra-small nanoparticles: boron carbon dots as drug candidates for boron neutron capture therapy. Issue 2 (8th December 2020) - Feiner, Irene V. J.; Pulagam, Krishna R.; Uribe, Kepa B.; Passannante, Rossana; Simó, Cristina; Zamacola, Kepa; Gómez-Vallejo, Vanessa; Herrero-Álvarez, Natalia; Cossío, Unai; Baz, Zuriñe; Caffarel, María M.; Lawrie, Charles H.; et al.
Abstract : Tetrazine-functionalised boron-rich carbon dots show fast clearance and enhanced tumour accumulation under pre-targeting conditions, as demonstrated using positron emission tomography. Abstract : Boron neutron capture therapy (BNCT) is a promising cancer treatment exploiting the neutron capture capacity and subsequent fission reaction of boron-10. The emergence of nanotechnology has encouraged the development of nanocarriers capable of accumulating boron atoms preferentially in tumour cells. However, a long circulation time, required for high tumour accumulation, is usually accompanied by accumulation of the nanosystem in organs such as the liver and the spleen, which may cause off-target side effects. This could be overcome by using small-sized boron carriers via a pre-targeting strategy. Here, we report the preparation, characterisation and in vivo evaluation of tetrazine-functionalised boron-rich carbon dots, which show very fast clearance and low tumour uptake after intravenous administration in a mouse HER2 (human epidermal growth factor receptor 2)-positive tumour model. Enhanced tumour accumulation was achieved when using a pretargeting approach, which was accomplished by a highly selective biorthogonal reaction at the tumour site with trans -cyclooctene-functionalised Trastuzumab.